1990
DOI: 10.1111/j.1365-2222.1990.tb02774.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intranasal nedocromil sodium on viral upper respiratory tract infections in human volunteers

Abstract: Two studies involving double-blind group comparative trials in human volunteers compared the effects of intranasal nedocromil sodium (2.6 mg active drug per nostril, q.i.d.) with placebo on clinical symptoms and performance impairment associated with the common cold. In the first study volunteers were challenged with rhinoviruses (RV9 and RV14), and in the second study with respiratory coronavirus. In both studies, active and placebo groups of volunteers were demographically similar. Infection rates in both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Bradykinin has been discovered in the nasal fluid during rhinovirus infections (Naclerio et al, 1987) and bradykinin challenge in the human nasal mucosa produces many of the symptoms seen during rhinovirus colds, including a sore throat (Proud et al, 1988). Interestingly, pretreatment with nedocromil sodium markedly reduces both secretion and symptom scores induced by rhinovirus infections in man (Barrow et al, 1990), which thus may be due to inhibition of bradykinin-induced activation of sensory nerves. The vasodilator response in the pig airways to i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin has been discovered in the nasal fluid during rhinovirus infections (Naclerio et al, 1987) and bradykinin challenge in the human nasal mucosa produces many of the symptoms seen during rhinovirus colds, including a sore throat (Proud et al, 1988). Interestingly, pretreatment with nedocromil sodium markedly reduces both secretion and symptom scores induced by rhinovirus infections in man (Barrow et al, 1990), which thus may be due to inhibition of bradykinin-induced activation of sensory nerves. The vasodilator response in the pig airways to i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that compounds which increase stimulation of the sensory afferent trigeminal nerve (e.g. zinc gluconate, Smith et al, 1991;nedocromil sodium, Barrow et al, 1990) can remove the malaise produced by experimentallyinduced URTIs. It was predicted that a hot drink would reduce the impairments associated with having a cold.…”
Section: Naturally Occurring Urtismentioning
confidence: 99%
“…Although antibody titres were used to confirm the presence or absence of the infection in indi viduals after challenge with virus [25], a correlation of these measures with performance has not been reported.…”
Section: Do Performance Effects Refect Underlying Pathology?mentioning
confidence: 99%